Optimizing Vibrant School Lampung Interactive Learning Media on Development Materials, Roots, and Logarithms - Hidayatulloh Hidayatulloh; Muhammad Kristiawan; Nurul Astuti Yensy B; Dina Apryanti; Noerhasmalina Noerhasmalina (STAI Hubbulwathan Duri, 2023)
This study aims to develop and analyze the effectiveness of PowerPoint learning media through the Smart School Lampung Berjaya virtual class application in improving the teaching and learning process, especially in development, roots, and logarithm material. This study used the ADDIE Development Research Model approach and was conducted at a state senior high school in Limau, Tanggamus Regency, with a sample of 30 students. Data collection techniques used observation, interviews, and tests, while data analysis techniques used qualitative research methods. Based on research, PowerPoint learning media products through the Smart School Lampung Berjaya virtual class application which have been validated by media experts, learning material experts, and mathematics teachers, as well as through student response tests, have proven effective in supporting the learning process. The results of this study indicate that the use of PowerPoint learning media through the Smart School Lampung Berjaya virtual class application can be a very effective tool in the teaching and learning process. The implication is that this media can be used to facilitate students' understanding of more complex material, such as development, roots, and logarithms, and can help increase the effectiveness of the teaching and learning process.